1987
DOI: 10.1164/ajrccm/136.1.188
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Alveolar Hypoventilation in a Six-Year-Old Girl with Intermittent Positive Pressure Ventilation Through a Nose Mask

Abstract: Persons with alveolar hypoventilation have abnormal daytime arterial blood gases and abnormal responses to hypercapnia and hypoxia in the absence of any identifiable lung or neuromuscular disease. The underlying defect in the control of breathing has not, however, been confirmed. We studied a 6-yr-old girl who was admitted in respiratory failure after a long history of disturbed breathing awake and asleep, which had been diagnosed as primary alveolar hypoventilation, (PaCO2 = 120). After several days of endotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…NIV, therefore, is considered as a highly effective treatment of chronic respiratory failure due to NMD and a consensus conference has recently published guidelines on the initiation of NIV including NMD [14]. Evidence of benefit, however, is only based on nonrandomised studies and remains scant in the paediatric setting, particularly in NMD other than DMD [15,16]. One earlier study of 10 children with nocturnal hypoventilation reported effective treatment but poor tolerance in patientsv10 yrs [17].…”
mentioning
confidence: 99%
“…NIV, therefore, is considered as a highly effective treatment of chronic respiratory failure due to NMD and a consensus conference has recently published guidelines on the initiation of NIV including NMD [14]. Evidence of benefit, however, is only based on nonrandomised studies and remains scant in the paediatric setting, particularly in NMD other than DMD [15,16]. One earlier study of 10 children with nocturnal hypoventilation reported effective treatment but poor tolerance in patientsv10 yrs [17].…”
mentioning
confidence: 99%
“…Author Study (n) Year of publication Population Akingbola et al (4) Case report (2) 1993 Children with atelectasis Fortenberry et al (5) Case series (28) 1995 Children with ARF Padman et al (6) Case series (34) 1998 Patients aged between 6 months and 18 years with ARF Sprague et al (7) Case series (5) 2000 Patients aged between 12 years and 18 years with ARF secondary to cystic fibrosis Akingbola et al (8) Case report (3) 2002 Children with asthma and hypercapnia Shah et al (9) Systematic review 2003 Children with bronchiolitis in ARF Thill et al (10) Randomized crossover clinical trial (16) 2004 Children with lower airways obstruction Piastra et al (11) Case series (4) 2004 Children aged between 9 and 17 years with acute leukemia and hypoxemic ARF Villanueva et al (12) Case series (23) 2005 Hypoxemic and hypercapnic ARF or respiratory failure after extubation Chin et al (13) Case series (15) 2005 Children aged 5 months and 14 years, submitted to liver transplant, that progressed with ARF and atelectasis Prado et al (14) Case series (14) 2005 Children aged between 1 month and 13 years, with ARF, reduced oxygenation (saturation < 93% with FiO2 > 40%) and ventilation (pH < 7,25), besides radiological impairment Carroll e Schramm (15) Case series (5) 2006 Children aged between 2 years and 18 years, with acute asthma, hypoxemia and increased respiratory work Essouri et al (16) Retrospective cohort (114 (20) Retrospective study 2007 Twenty patients with mean ages of 7.4 years, with ARF, received NIV and were divided into two groups for analysis: hypoxic and hypercapneic group. Codazzi et al (21) Case series (15) 2006 Fifteen children from 1 month to 5 years with hypoxemic ARF Piastra et al hypoxic group and hypercapnic group.…”
Section: Stregth Of Recommendationmentioning
confidence: 99%
“…In 1987, the first use of NIV with a nasal mask was recorded in a six-year-old child with a primary diagnosis of alveolar hyperventilation (2) . Over the last 20 years, the number of experiences with the use of NIV in children has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…When daytime respiratory insufficiency is present, tracheostomy is an option. A few studies [29,[71][72][73][74] have demonstrated beneficial effects such as improved oxygenation and ventilation from the long-term use of NIV in Ondine9s curse, including children from the age of 7 weeks to teenagers, who in the latter case have been converted from invasive ventilation.…”
Section: Central Hypoventilation Disordersmentioning
confidence: 99%